Nanoengineered Neutrophils as a Cellular Sonosensitizer for Visual Sonodynamic Therapy of Malignant Tumors - Sun, Lei; Zhou, Jing‐e; Luo, Tengshuo; Wang, Jing; Kang, Liqing; Wang, Yeying; Luo, Shenggen; Wang, Zhehao; Zhou, Ziyu; Zhu, Jiaxi; Yu, Jiahui; Yu, Lei; et al. (Advanced materials (Weinheim), 2022)
The rapid evolution of cell‐based theranostics has attracted extensive attention due to their unique advantages in biomedical applications. However, the inherent functions of cells alone cannot meet the needs of malignant tumor treatment. Thus endowing original cells with new characteristics to generate multifunctional living cells may hold a tremendous promise. Here, the nanoengineering method is used to combine customized liposomes with neutrophils, generating oxygen‐carrying sonosensitizer cells with acoustic functions, which are called Acouscyte/O2, for the visual diagnosis and treatment of cancer. Specifically, oxygen‐carried perfluorocarbon and temoporfin are encapsulated into cRGD peptide modified multilayer liposomes (C‐ML/HPT/O2), which are then loaded into live neutrophils to obtain Acouscyte/O2. Acouscyte/O2 can not only carry a large amount of oxygen but also exhibits the ability of long circulation, inflammation‐triggered recruitment, and decomposition. Importantly, Acouscyte/O2 can be selectively accumulated in tumors, effectively enhancing tumor oxygen levels, and triggering anticancer sonodynamics in response to ultrasound stimulation, leading to complete obliteration of tumors and efficient extension of the survival time of tumor‐bearing mice with minimal systemic adverse effects. Meanwhile, the tumors can be monitored in real time by temoporfin‐mediated fluorescence imaging and perfluorocarbon (PFC)‐microbubble‐enhanced ultrasound imaging. Therefore, the nanoengineered neutrophils, i.e., Acouscyte/O2, are a new type of multifunctional cellular drug, which provides a new platform for the diagnosis and sonodynamic therapy of solid malignant tumors. Nanoengineered neutrophil sonosensitizers are developed for visual sonodynamic therapy (SDT) of solid malignant tumors. Acouscyte/O2 not only has an enhanced multilevel active targeting but also provides oxygen to enhance SDT effects to eliminate tumors, maintain the appearance, and real‐time multimode imaging, which provides a promising theranostic strategy for solid malignant tumors.